FLAVONOID CONTENT AND ANTIOXIDANT ACTIVITY OF Camellia sinensis KOMBUCHA ETHYL ACETATE EXTRACT AND CREAM FORMULATION - Bethasari, Maulidwina; Rahayu, Anis Puji; Safitri, Novis (Universitas Muhammadiyah Ahmad Dahlan Cirebon, 2025)
Kombucha, a fermented tea beverage made using a symbiotic culture of bacteria and yeast (SCOBY), is gaining interest due to its bioactive compounds, particularly flavonoids, which are known for their antioxidant properties. These natural antioxidants, derived from the tea leaves of Camellia sinensis, may offer functional benefits when applied in topical formulations such as creams. This study aimed to determine the flavonoid concentration in kombucha extracts after fermentation for 7 and 14 days and to evaluate the antioxidant activity of a cream formulation containing kombucha extract. Kombucha extract was obtained using a liquid-liquid extraction method with ethyl acetate as the solvent. Antioxidant activity was measured using the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay, where a lower IC50 value indicates stronger antioxidant activity. The results showed that The total flavonoid content in the kombucha extract fermented for 7 days (H7) was 125.79 ± 0.192 mg QE/g, while the extract fermented for 14 days (H14) contained 35 ± 0.333 mg QE/g. Antioxidant activity testing revealed IC50 values of 6.84 for the H7 extract and 7.48 for the H14 extract, indicating that the 7-day fermented kombucha had a higher antioxidant potential. These findings suggest that fermentation duration significantly affects the flavonoid content and antioxidant capacity of kombucha extracts, which may influence their efficacy when incorporated into topical formulations, such as creams. This study highlights the potential of kombucha extracts as natural antioxidant agents for cosmetic and pharmaceutical applications. Keywords: antioxidant, Camellia sinensis, flavonoid, kombucha, SCOBY